Insights for the hydrogen-mediated deoxydehydration (DODH) with Cp*ReO3 and alkene extrusion of related Re(V)-diolates - Stöckl, Yannick; Rominger, Frank; Hashmi, A. Stephen K.; Schaub, Thomas (ChemCatChem, 2025)
To transform highly oxygenated molecules such as polyols from biomass into value-added chemicals, the deoxygenation via the deoxydehydration (DODH) is a promising approach. We report the catalytic DODH of substrates from renewable resources using Cp*ReO3 (1 mol%, TON up to 32) as a catalyst and hydrogen as a reductant. Additionally, the synthesis of Re(V)-diolates is described for tartrates, glycerol and erythritol derivatives. These Re(V)-diolates were obtained in 35-53% yield and as mixtures of diastereomers. Their characterization was accomplished using 2D NMR, MS, IR and X-ray diffraction. A NOESY study revealed an intermolecular exchange of glycerol moieties for the diolate complex. Further, alkene extrusion experiments allowed us to establish a reactivity order for a variety of substituents. The olefin extrusion was the fastest for tartrate units and the slowest for glycerol and erythritol diolates.